Dielectric Material - Alexandru Silaghi, Marius (IntechOpen, 2012)
This book attempts to bring together the theory and practice of dielectric materials for different kind of industrial applications. Fragmented information on dielectric theory and properties of materials, design of equipment and state of the art in applications relevant to the manufacturing industry should be collated and updated and presented as a single reference volume. In this book relevant and useful information is presented in the quoted literature and covered by our key patent applications.